English skills with readings - Langan, John (New York McGraw-Hill, 2008)
Basic principles of effective writing; Paragraph development; Essay development; Research skills; Handbook of sentence skills; Readings for writers.
Includes index.
Keywords: English language -- Rhetoric; English language -- Grammar; College readers; Tiếng Anh